Spatial clustering patterns and regional variations for food and physical activity environments across the United States. Issue 8 (17th November 2021) - Wende, Marilyn E.; Stowe, Ellen W; Eberth, Jan M.; McLain, Alexander C.; Liese, Angela D.; Breneman, Charity B.; Josey, Michele J.; Hughey, S. Morgan; Kaczynski, Andrew T.
ABSTRACT: This study examined spatial patterns of obesogenic environments for US counties. We mapped the geographic dispersion of food and physical activity (PA) environments, assessed spatial clustering, and identified food and PA environment differences across U.S. regions and rurality categories. Substantial low food score clusters were located in the South and high score clusters in the Midwest and West. Low PA score clusters were located in the South and high score clusters in the Northeast and Midwest (p < .0001). For region, the South had significantly lower food and PA environment scores. For rurality, rural counties had significantly higher food environment scores and metropolitan counties had significantly higher PA environment scores (p < .0001). This study highlights geographic clustering and disparities in food and PA access nationwide. State and region-wide environmental inequalities may be targeted using structural interventions and policy initiatives to improve food and PA access.